Immuno- and hemocompatibility of amino acid pairing peptides for potential use in anticancer drug delivery. (May 2014) - Naahidi, Sheva; Jafari, Mousa; Logan, Megan; Edalat, Faramarz; Khademhosseini, Ali; Dixon, Brian; Chen, Pu
Amino acid pairing peptide-based nanoparticles were recently introduced as promising carriers for hydrophobic anticancer drugs. The AC8 peptide, n-FEFQFNFK-c, is based on the amino acid pairing (AAP) design with 8 amino acids and hence the designated name AAP8. The nanoparticles (NPs) AAP8 have modified either on the C-terminal or on both terminal, by conjugation with diethylene glycol (DEG) . Here, the in vitro biocompatibilities of the NPs and their modified versions were compared and the potential of these NPs as carriers for the hydrophobic anticancer drug pirarubicin was determined as well as the peptide-drug co-assembly complexes. The toxicity of the NPs, DEGylated NPs, and blended mixtures with pirarubicin, was tested against the human adenocarcinoma lung cancer cell line, A549. The amino-end DEGylated NP, (NP-I), had superior biocompatibility over the non-modified NPs or double DEGylated NPs (NP-II). NP-I had very low hemolytic activity (1%) while NP and NP-II had marginal (8%) and acceptable (5%) hemolytic activity, respectively. All three types of NPs did not activate the complement system via the classical and alternative pathways nor did they activate the anaphylotoxin C3a. However, NP-II and its drug complex effectively activate the complement terminal attack complex. The lectin pathway was not activated by NP-I and NP-II, but was to a small extent by the non-modified NPs, with no lectin activation when complexed with drug. These results indicate NP-I is the most promising peptide for use as a drug delivery system, highlighting the importance of proper modification in peptides for drug delivery systems.